1999
DOI: 10.1042/0264-6021:3410051
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression of Pen c 2, a novel allergen from Penicillium citrinum

Abstract: The mould genus, Penicillium, is known to be a significant source of environmental aero-allergens. One important allergen from Penicillium citrinum, Pen c 2, has been identified by means of two-dimensional immunoblotting using IgE-containing patients' sera. This novel allergen was cloned, sequenced and expressed in Escherichia coli. The cloned cDNA encodes a large 457-amino acid protein precursor containing a 16-amino acid signal peptide, a 120-amino acid propeptide and the 321-amino acid mature protein. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Der p 1, which is a cysteine proteinase [32], and Der p 3, Der p 6, and Der p 9, which are serine proteases [33][34][35]. Moreover, we previously reported that the major allergens Pen c 1 and Pen c 2 in P. citrinum are also serine proteases [17,18]. The epithelium-detaching protease activity of allergens is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Der p 1, which is a cysteine proteinase [32], and Der p 3, Der p 6, and Der p 9, which are serine proteases [33][34][35]. Moreover, we previously reported that the major allergens Pen c 1 and Pen c 2 in P. citrinum are also serine proteases [17,18]. The epithelium-detaching protease activity of allergens is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The sense primer used was 5h-GCCTTGACCACTCAAAAGGGC-3h, coding for the seven N-terminal amino acids, and the antisense primer was 5h-TGA-GGGGTGGCCATGGAAGTA-3h for the active site region. To obtain the 5h and 3h portion of the Asp f 13 cDNA, the RACE PCR protocol was used as described previously [17]. The coding sequence of the Asp f 13 gene was thus amplified by PCR and the amplified product analysed by electrophoresis and subcloned into the pGEM-T vector (Promega).…”
Section: Preparation Of Mrna From a Fumigatus Pcr Amplification Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The sense primer used was 5Ј-GCTGACGCTGCTGT(T/C)ATTGA(A/G)AAG-3Ј, encoding the eight N-terminal amino acids (ADAAVIEK), while the antisense primer was 5Ј-GCGGTC(G/A)TGGTG(A/T)GAGAA(A/G)GGAAT-3Ј, encoding a conserved sequence of amino acids (IPFSHHDR) found in arginine kinases. To obtain the 5Ј and 3Ј portions of the Pen m 2 cDNA, the RACE PCR protocol was used as described previously (26). The coding sequence of the Pen m 2 gene was then amplified by PCR, and the amplified product analyzed by electrophoresis and subcloned into the pGEM-T vector, then transformed into Escherichia coli strain JM109.…”
Section: Isolation Of Mrna Cdna Cloning and Sequencingmentioning
confidence: 99%
“…Crude extracts were analyzed by 2-D immunoblotting as described previously (26). Briefly, for the first separation, 0.5 mg of P. monodon extract was applied to an immobilized pH gradient gel strip containing pH range of 3-10 ampholytes, and isoelectric focusing was performed in a Multiphor II horizontal electrophoresis system (Amersham Pharmacia Biotech).…”
Section: -D Immunoblottingmentioning
confidence: 99%